Pengembangan Prototype Sistem Keamanan Rumah Berbasis Android Dan Mikrokontroler - Johan, T. Muhammad (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2023)
The current industrial revolution is marked by the emergence of various computer-based devices with certain specifications to be used to complete certain jobs. This device was born from the development of computers, which were originally devices used to complete simple calculations, with large sizes and required high development costs. Gradually through various studies, a new computer technology was born which has a small size, low power consumption, low development costs and has a much more optimal and intelligent performance. One of the technologies in question is the home security system developed in this study. This system can operate with 4 units of AA batteries connected to the microcontroller and android smartphone. The system built is able to solve the problems that exist in conventional door security systems that use physical locks with the following weaknesses: 1) Physical locks that are easily damaged; 2) Keys are easy to lose; 3) Limited keys, because door lock manufacturers only provide 3-4 spare keys, which means one set of keys can only be used by 3-4 users; 4) Security is not guaranteed, because currently physical keys can be easily duplicated by locksmiths on the market today. The results of this study are the development of a prototype home security system using an Android smartphone and a microcontroller. The user only needs to access the system via an Android smartphone, then the system will authorize the user, if the user is an authorized user, the system will forward the command to the relay to deactivate the selenoid door lock. The built system also has an alarm feature that is generated by a buzzer when an entry attempt is made by an unregistered device